PREVALENCE DES MALADIES INFANTILES DUES AUX DETERMINANTS SANITAIRES ET ENVIRONNEMENTAUX A KASONGO AU MANIEMA EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Timothée, KIMPUTU KABALA; Jean , LUAMBA LUA NSEMBO; Déogratias, MUTAMBEL’HITY (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The survey of prevalence of the infantile illnesses due to the sanitary and environmental determinants to Kasongo in the Maniema in RD Congo during one quinquennial period of 2017 to 2021, permitted to analyze the prevalence of the morbidity, to count and to diagnose the MID to the laboratory. The MID are grouped in four categories notably the bacterial illnesses, the parasitic illnesses, the viral illnesses and the nutritional illnesses The environmental determinants influencing the MID to Kasongo are provision in water of drink, purification, hygiene and the malnutrition.